Hubungan kemampuan numerik dan kemampuan spasial terhadap kemampuan komunikasi matematis siswa - Bedilius Gunur; Derfina Agustavira Lanur; Polikarpus Raga (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2019)
Penelitian ini bertujuan untuk mendeskripsikan (1) hubungan parsial antara kemampuan numerik dan kemampuan spasial dengan kemampuan komunikasi matematis siswa; (2) hubungan kemampuan numerik dan kemampuan spasial secara simultan terhadap kemampuan komunikasi matematis siswa. Penelitian ini merupakan penelitian korelasional dengan populasi adalah siswa kelas VII SMPK Santu Fransiskus Xaverius Ruteng yang terletak di Kecamatan Langke Rembong Kabupaten Manggarai, Propinsi Nusa Tenggara Timur. Sampel sebanyak 66 siswa dipilih menggunakan teknik random sampling. Data diperoleh dari tes kemampuan numerik, tes kemampuan spasial, dan tes kemampuan komunikasi matematis. Analisis uji prasyarat menggunakan uji normalitas, uji linearitas, dan uji multikolinearitas. Analisis data menggunakan analisis korelasi sederhana dan korelasi ganda. Hasil penelitian menunjukkan bahwa (1) terdapat hubungan signifikan antara kemampuan numerik dengan kemampuan komunikasi matematis siswa dengan koefisien korelasi 0,457 dan besar sumbangan kemampuan numerik terhadap kemampuan komunikasi matematis sebesar 20,9%; (2) terdapat hubungan signifikan antara kemampuan spasial dengan kemampuan komunikasi matematis siswa dengan koefisien korelasi 0,426 dan besar sumbangan kemampuan spasial terhadap kemampuan komunikasi matematis sebesar 18,1%; (3) terdapat hubungan signifikan kemampuan numerik dan kemampuan spasial secara simultan terhadap kemampuan komunikasi matematis siswa dengan koefisien korelasi 0,555 dengan kontribusi kedua variable secara simultan terhadap kemampuan komunikasi matematis siswa sebesar 30,8%. The relationship between numerical and spatial ability to students' mathematical communication ability AbstractThis study aimed to describe (1) a partial relationship between students’ numerical abilities and spatial abilities with mathematical communication abilities; (2) simultaneous relationship between students’ numerical and spatial abilities to mathematical communication abilities. This study used correlational research. The population of this research was seventh-grade students of SMPK St. Fransiskus Xaverius Ruteng, located in Langke Rembong Subdistrict, Manggarai Regency, East Nusa Tenggara, Indonesia. A sample of 66 students was selected using the random sampling technique. Data were obtained by using numerical ability tests, spatial ability tests, and mathematical communication ability test. Before analyzing the data, a normality test, linearity test, and multicollinearity test were carried out. The data were analyzed by using a simple correlation and multiple correlations. Data analysis showed that (1) there was a significant relationship between students’ numerical abilities and mathematical communication abilities with correlation coefficient 0,457 and the contribution of numerical ability to mathematical communication ability was 20.9%; (2) there was a significant relationship between students’ spatial abilities and mathematical communication abilities with correlation coefficient 0,426 and the contribution of spatial ability to mathematical communication ability is 18.1%; (3) there was a simultaneous relationship between students’ numerical and spatial abilities to students mathematical communication abilities with correlation coefficient 0,555 with the contribution of both variables to students' mathematical communication ability was 30.8%.